Let me present you a derivation which does not use the circular assumption presented in the "dart" proof and uses only the property of the Central limit theorem - i.e. that for any suitable set of i.i.d. variables $\{ X_1,X_2,\ldots,X_n \}$ with $\mathrm{E}\left[X\right]=\mu$ and $\mathrm{Var}\left[X\right]=\sigma^2$, we have
$$Z_n := \frac{\bar{X}-\mu}{\sigma/\sqrt{n}} \overset{n\rightarrow\infty}{\longrightarrow} Z \sim N(0,1)$$
where $N(0,1)$ is the so called normal distribution (of the variable $Z$). Central limit theorem provides us the universality, i.e. no matter which set we choose, we will allways get $Z\sim N(0,1)$ - the same distribution. From this universality only we will find the formula for the distribution function $f(z)$ of the standard normally distributed $Z$. Any other normal variable $X \sim N(\mu,\sigma)$ is get from $Z$ by scalling and its density function must be $f\left((x-\mu)/\sigma\right)/\sigma$.
1) Stirling approximation
Without proof (can be found elsewhere) we state that for large $n$ we have
$$n! \approx \sqrt{2\pi n}\left(\frac{n}{e}\right)^n$$
2) Poisson distribution
The key to derive the normal distribution density function is to choose some particular set of i.i.d. for which we can find the density function of its sum (average $\bar{X}$ is that sum divided by $n$), i.e. to choose $X_1$. There are multiple choices for such choice, in many derivation of normal distribution function it is common to choose $X_1 \sim \mathrm{Ber}(p)$ Bernoulli, so the sum $S_n = X_1 + X_2 + \ldots + X_n \sim \mathrm{Bin}(n,p)$ is Binomial. In our approach, we set $X_1 \sim \mathrm{Po}(1)$. Random variable $X$ with a Poisson distribution $\mathrm{Po}(\lambda)$ has the known discrete distribution function:
$$\mathbb{P}\left[X = k\right]=\frac{\lambda^k}{k!}e^{-\lambda}, \qquad k=0,1,2,\ldots$$
Moreover $\mathrm{Var}\left[X\right] = \lambda$. For $X_1 \sim \mathrm{Po}(1)$ we have $\mu = \lambda = 1$ and $\sigma = \sqrt{\lambda} = 1$.
Poisson distribution is the distribution of the number $X$ of uniformly distributed events in a given finite time interval with a given $\lambda = \mathrm{E}\left[X\right]$ average number of events.
We have chosed the Poisson distrubition because of one special property - aditivity. One can think of the sum of two identical (same $\lambda$) independent poisonian $X_1 + X_2$ as the number of the same events it an interval with twice the duration of the previous one. Since
$$\mathrm{E}\left[X_1+X_2\right]=\mathrm{E}\left[X_1\right]+\mathrm{E}\left[X_2\right]=1 + 1 = 2$$
we immediately get (using the "events" description of Poisson distribution), that also
$$S_n = X_1 + X_2 + \ldots + X_n \sim \mathrm{Po}(n)$$
This distribution is discrete with again the step equal to $1$. However, on the left hand side of CLT we get
$$Z_n = \frac{\bar{X}-\mu}{\sigma/\sqrt{n}} = \frac{S_n - n}{\sqrt{n}}$$
Clearly, $S_n$ is reduced by $n$ and then divided by $\sqrt{n}$. This division causes the $\mathrm{Po}(n)$ in the limit of $n\rightarrow\infty$ be continuous, since now the step is $1/\sqrt{n}$ and this covers eventually all the real numbers.
Consider now the limit of large $n$. Let $z$ be a real number. We can write $z=(k-n)/\sqrt{n}$ (for large $k$ and $n$ natural, in a sense of being close to original real $z$). Then, using the definition of (continuous) distribution function
$$f(z)\approx\frac{1}{1/\sqrt{n}}\left(\mathbb{P}\left[Z_n < z + \frac{0.5}{\sqrt{n}}\right]-\mathbb{P}\left[Z_n < z - \frac{0.5}{\sqrt{n}}\right]\right)=\sqrt{n}\,\mathbb{P}\left[Z_n = z\right]$$
since there is only one point $z$ in the interval $(z-0.5/\sqrt{n},z+0.5\sqrt{n})$. But since
$$\mathbb{P}\left[Z_n = z\right] = \mathbb{P}\left[\frac{S_n - n}{\sqrt{n}} = \frac{k - n}{\sqrt{n}}\right]=\mathbb{P}\left[S_n = k\right]=\frac{n^k}{k!}e^{-n}$$
In the limit $n\rightarrow\infty$ with $k = n + z\sqrt{n}$ we then have explicitely
$$f(z) = \lim_{n\rightarrow \infty} \sqrt{n}\frac{n^{n + z\sqrt{n}}}{(n + z\sqrt{n})!}e^{-n}$$
Using Stirling's approximation
$$f(z) = \lim_{n\rightarrow \infty} \sqrt{n}\frac{e^{n + z\sqrt{n}}}{\sqrt{2\pi (n + z\sqrt{n})}}\left(\frac{n + z\sqrt{n}}{n}\right)^{-n - z\sqrt{n}}e^{-n} = \frac{1}{\sqrt{2\pi}}\lim_{n\rightarrow \infty} e^{z\sqrt{n}}\left(1+\frac{z}{\sqrt{n}}\right)^{-n - z\sqrt{n}}$$
3) Exponential function limit
This can be further simplified using the well known
$$e^x = \lim_{n\rightarrow \infty}\left(1+\frac{x}{n}\right)^n$$
i.e. for example
$$\lim_{n\rightarrow \infty} \left(1+\frac{z}{\sqrt{n}}\right)^{- z\sqrt{n}} = e^{-z^2}$$
therefore
$$f(z) = \frac{e^{-z^2}}{\sqrt{2\pi}}\lim_{n\rightarrow \infty} e^{z\sqrt{n}}\left(1+\frac{z}{\sqrt{n}}\right)^{-n}$$
The last limit is performed by Taylor expansion of logarithm since
$$\lim_{n\rightarrow \infty} e^{z\sqrt{n}}\left(1+\frac{z}{\sqrt{n}}\right)^{-n} = \exp\left(\lim_{n\rightarrow \infty} z\sqrt{n}-n\ln\left(1+\frac{z}{\sqrt{n}}\right)\right) = \exp\left(\lim_{n\rightarrow \infty} z\sqrt{n}-z\sqrt{n}+\frac{z^2}{2}\right)$$
imediately recovering
$$f(z) = \frac{1}{\sqrt{2\pi}} e^{-\frac{z^2}{2}}$$